2013
DOI: 10.1016/j.infoecopol.2013.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Investment in customer recognition and information exchange

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…Our evaluation of information exchange shares this perspective with Liu and Serfes (), Jentzsch et al. (), and Shy and Stenbacka (). However, we evaluate information exchange within the framework of a more general analysis of different degrees of privacy protection, whereas in Liu and Serfes () and Jentzsch et al.…”
Section: Introductionsupporting
confidence: 64%
See 1 more Smart Citation
“…Our evaluation of information exchange shares this perspective with Liu and Serfes (), Jentzsch et al. (), and Shy and Stenbacka (). However, we evaluate information exchange within the framework of a more general analysis of different degrees of privacy protection, whereas in Liu and Serfes () and Jentzsch et al.…”
Section: Introductionsupporting
confidence: 64%
“…Our model evaluates information exchange from a very different perspective, namely as a mechanism to expand the firms' knowledge of consumer-specific preferences, conditional on which the firms can fine-tune targeted pricing. Our evaluation of information exchange shares this perspective with Liu and Serfes (2006), Jentzsch et al (2013), and Shy and Stenbacka (2013). However, we evaluate information exchange within the framework of a more 5.…”
Section: Introductionmentioning
confidence: 99%
“…As in the present paper, Liu and Serfes (2004) have found that moving from no discrimination (no information) to discrimination is bad for industry profits and good for consumer surplus. However, conditional on the availability of information, they have 14 For other recent papers on BBPD and customer recognition, see also Caillaud and De Nijs (2011), Chen and Pearcy (2010), Esteves (2010), Esteves and Vasconcelos (2014), Esteves and Reggiani (2014), Gehrig et al (2011Gehrig et al ( , 2012, Ghose and Huang (2009), Ouksel and Eruysal (2011, 2013. 15 They define targetability as a firm's ability to predict the preferences and purchase behaviors of individual consumers.…”
Section: Related Literaturementioning
confidence: 99%
“…In the current analysis, firms know that their products are substitutes, and information sharing enables them to refine their knowledge regarding each consumer's preferences. Shy and Stenbacka (2013) investigate how information exchange affects the incentives of firms to invest in the costly acquisition of information on customers tastes. They show that the exchange of acquired information is bad for firms' profits and hurts consumers, but that such exchanges do not occur in equilibrium.…”
Section: Introductionmentioning
confidence: 99%